Application of the Revegetation Sheet with the Erosion Control Function to the Expansive Clay Soil Slope -A Case Study on Test Construction and Monitoring in West Java, Indonesia- - Kohno, Nobuyuki; Shimizutani, Takashi (International Journal of Biosciences and Biotechnology, 2016)
A new type of revegetation sheet which also has a function of soil erosion control was applied to the expansive clay soil slope in West Java, Indonesia, and the function of the sheet to reduce the collapse of the slope was examined. Firstly, it was identified that the soil in the test construction site was a typical expansive clay soil mainly consisting of smectite and quartz according to the X-ray diffraction analysis. Secondly, as a result of monitoring up to 13 months after the application of the sheet, it was observed that the sheet successfully controlled soil erosion and led to gradual vegetation recovery, despite the fact that the construction area is in a part of tropical monsoon climate where the rainy and the dry seasons come repeatedly in a year and the soil swells in rainy season and shrinks and forms crack in dry season. Therefore, it was indicated that as the recovery of vegetation went by, the effect of controlling soil erosion, land slide and slope collapse would be increased.
Keywords: erosion control; revegetation sheet; clay soil slope